The Influence Of Visual, Auditory, Kinesthetic (Vak) Learning Models On The Akidah Aklaq Subject Learning Outcomes - Jaziela Huwaida; Nada Mudrikah al Khudary; Saiful Anwar (Prodi PAI, Fakultas Tarbiyah, UNIDA GONTORs Tarbiyah, Universitas Darussalam Gontor, 2025)
Akidah akhlak is a science that studies the beliefs and beliefs that Muslims must believe in because this will shape one's attitude and behavior because moral formation is upheld in Islamic education. In learning Akidah Akhlak material at the Miftahul Jannah Islamic Boarding School, teaching still uses a conventional approach with the lecture method which causes the achievement of learning to not be achieved, so researchers are trying to provide a VAK learning model with Akidah Akhlak material in the Adab chapter in getting along. The purpose of this study was to determine the effect of the Visual, Auditory, Kinesthetic (VAK) Learning Model on Akidah Akhlak Learning Outcomes of Grade 9 Miftahul Jannah Mantingan Islamic Boarding School. This study uses a quantitative approach experimental method Pretest-Posttest Control Group Design with Probability Sampling sampling technique with Simple Random Sampling type. Researchers took samples of learning outcomes from 20 students in each experimental class and control class with a total of 40 students. In the data collection technique, researchers used tests, documentation, and interviews, while in data analysis researchers used SPSS 25 to obtain the results of the Independent test calculation. The results showed that there was an effect of the Visual, Auditory, Kiesthetic (VAK) Learning Model on the Learning Outcomes of Akidah Akhlak Class 9 of Miftahul Jannah Mantingan Islamic Boarding School